Optimisation of Injection Moulding Process Parameter Using Taguchi and Desirability Function - Vivekanandan, Panneerselvam; Faiz, Mohd Turan (Springer, 2021)
The main goal of conducting this research is to primarily investigate the effects of injection moulding parameters on the mechanical properties of plastic part made of recycled plastic. In order to achieve the goal, the significant process parameter is identified with a proper research on previous studies. The mechanical properties of the specimens are measured in term of tensile strength and flexural modulus respectively. Instead of focusing on single quality characteristic, this research also proposed multi response optimization by integrating Taguchi method and desirability functions. The optimal processing parameters and the significance of each processing parameter on the mechanical properties of part produced are determined. From the experimental analysis and results, it is shown that the most significant processing parameter affecting the tensile strength is melt temperature, injection time and holding, time. The most effective process parameter on flexural modulus is melt temperature, holding time and injection pressure. The best set of process parameter are 180 °C of melt temperature, 55 MPa injection pressure, 30 mm/s injection speed, 8 s injection time, 20 MPa holding pressure, 3 s holding time and 25 s cooling time. This parameter will optimise the part quality to 199 kgf/cm2 of tensile strength and can result in flexural modulus of 10005 kgf/cm2. From the integration of Taguchi optimization processes and desirability function, the mechanical performances exhibited by the part made of recycled plastic have shown that recycled materials are potentially substituted for virgin material.